α-Bisabolol protege da lesão cerebral isquêmica, por um mecanismo que envolve inibição da inflamação e do estresse oxidativo - Fernandes, Mara Yone Soares Dias (2019)
The pathophysiology of stroke involves the reduction blood supply, a condition of hypoxia and glucose deprivation, which causes excitotoxicity, oxidative stress, apoptosis and tissue damage in the affected region. Stroke is the second leading cause of death worldwide and one of the leading causes of physical disability in adults. Α- Bisabolol (α-bis) is a monocyclic sesquiterpene alcohol that has shown antioxidant, anti-inflammatory and anti-apoptotic activity. The objective of the present study was to evaluate the effects of α-bis on neuronal damage (TTC and motor deficit), memory deficits, apoptosis, inflammatory response, oxidative stress and synaptic plasticity of mice submitted to cerebral ischemia. Permanent occlusion of the middle cerebral artery (pMCAO) was the in vivo used to induce ischemia. Α-bis was administered orally 3 h after pMCAO and / or once daily for up to 3 days depending on the experimental design. Ischemic damage was assessed 24 hours after surgery by TTC staining and neurological assessment. Α-Bisabolol significantly decreased infarct area and sensorimotor performance of animals submitted to pMCAO. Locomotor activity and motor coordination were assessed 72 hours after pMCAO through the open field test and the rotarod test, and a reduction in horizontal and vertical exploration capacity and motor coordination was observed in ischemic animals compared with The FO group, and α-bis treatment, protected against these deficits in the open field test. Memory deficits were evaluated by Y-maze and passive avoidance tests and we observed that ischemic animals had working and aversive memory deficits, and treatment with α-bis prevented these memory deficits. Apoptosis pathways were evaluated by the relative density of cytochrome c, pro-caspases-3, -9, and caspases -3, -9, total and cleaved PARP. To explore the likely underlying mechanism of the α-bis neuroprotective effect, hippocampal slices were subjected to oxygen and glucose deprivation (OGD) for 7 min to mimic ischemic injury in vitro. Our results showed that in physiological situations, α- bisabolol did not change: basal synaptic transmission, short (PPF) and long duration (LTP and depotentiation) plasticity. In the presence of OGD, α-bisabolol prevented irreversible depression of fEPSP (excitatory postsynaptic potential) compared with the control group. The oxygen uptake rate was assessed using the orbital equipment, and we observed that animals subjected to OGD and vehicle treated (0.01% ethanol) had a burst in respiration (increased oxygen uptake rate) in the first minutes, which over time decreased, and treatment with α-bis prevented the onset of this burst in breathing. Neuroinflammation was assessed by immunostaining for IL-1β, TNF-α, relative density of NF-κB, and biochemical test for MPO. Treatment with α-bis significantly reduced these inflammatory markers. In addition, oxidative stress was also evaluated by the relative density of SOD-2 protein and by biochemical tests for nitrate / nitrite and TBARS. Our results showed increased relative density of SOD-2 protein in the α-bis treated groups; We concluded that α-bisabolol showed neuroprotective activity probably due to its anti-inflammatory, antioxidant and antiapoptotic action providing us with experimental evidence about its use as an adjuvant in the treatment of cerebral ischemia.